2015
DOI: 10.1002/bit.25620
|View full text |Cite
|
Sign up to set email alerts
|

A multi‐pronged investigation into the effect of glucose starvation and culture duration on fed‐batch CHO cell culture

Abstract: (2015). A multi-pronged investigation into the effect of glucose starvation and culture duration on fed-batch CHO cell culture. Biotechnology and Bioengineering (Print), 112(10), 2172-2184. https://doi.org/10.1002/bit.25620 Accepted PreprintThis article is protected by copyright. All rights reserved Accepted PreprintThis article is protected by copyright. All rights reserved AbstractIn this study, omics-based analysis tools were used to explore the effect of glucose starvation and culture duration on monoclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 43 publications
4
62
0
Order By: Relevance
“…This is supported by the current literature, in which galactosylation levels of IgG are typically reported to be lower than 60%. This suggests that the speed of the glycoproteins through the Golgi, and therefore, the time the enzyme can interact with the glycan, might be critical (Fan et al, 2015). Gramer et al (2011) galactosylated species and, therefore, confirmed the possibility of obtaining high galactosylation levels in vitro.…”
Section: Galactosylation and Sialylationmentioning
confidence: 54%
See 1 more Smart Citation
“…This is supported by the current literature, in which galactosylation levels of IgG are typically reported to be lower than 60%. This suggests that the speed of the glycoproteins through the Golgi, and therefore, the time the enzyme can interact with the glycan, might be critical (Fan et al, 2015). Gramer et al (2011) galactosylated species and, therefore, confirmed the possibility of obtaining high galactosylation levels in vitro.…”
Section: Galactosylation and Sialylationmentioning
confidence: 54%
“…This was calculated for both the exponential and the stationary phase following the equation published by Fan et al (2015): This was calculated for both the exponential and the stationary phase following the equation published by Fan et al (2015):…”
Section: Purification and Analysis Of The Glycosylation Profilementioning
confidence: 99%
“…This bottleneck is due to a slowdown in the transfer of galactose and sialic acid residues to the glycoproteins and is unlikely to be caused by loss of productivity (which was nearly identical on day 10 and 14). Fan et al () demonstrated that a slowdown in glycan processing occurred with increased culture duration despite an abundance of nucleotide sugar donors, however this may not necessarily be true in our case due to differences in cell line and cell culture conditions used. It is also plausible that the bottleneck is caused either by an imbalance in the level of expression of glycosyltransferases or breakdown of relevant complexes (Kellokumpu et al, ) due to changes in cell culture conditions.…”
Section: Discussionmentioning
confidence: 67%
“…process information (such as viable cell density, productivity) to increase the mechanistic knowledge by integrating further important characteristics besides the media composition in the framework of glycosylation modulation 122,[280][281][282] . At later stages of process development, such additional (dynamic) characteristics are likely to play a key role in building predictive process models.…”
Section: Discussionmentioning
confidence: 99%